Revisit to carbon monoxide oxidation on Pd(111) surfaces - Nagarajan, Sankaranarayanan; Thirunavukkarasu, Kandasamy; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2009)
Carbon monoxide (CO) oxidation on Pd(111) surfaces has been studied by molecular beam methods with mixed molecular beams (CO + O(2)) between 400 and 900 K and a CO:O(2) ratio of 7:1 to 1:10. A new aspect of the above reaction observed in the transient kinetics regime is the evidence for oxygen diffusion into Pd(111) subsurface layers and its significant influence toward CO oxidation at high temperatures (>= 600 K). An overall influence of subsurface oxygen on the kinetics of the CO oxidation reaction is addressed. Interesting information derived from the above studies is the necessity to fill up the subsurface layers with oxygen atoms to a threshold coverage (theta(Osub)), above which the reactive CO adsorption occurs on the surface with subsequent CO(2) production. The above observation Was demonstrated with CO-rich reactant compositions (CO + O(2)) above 600 K via instant oxygen adsorption on Pd surfaces; however, onset of CO adsorption as well as CO(2) production occurs after a time delay. theta(Osub) and the time delay in CO adsorption (and CO(2) production) increase with increasing temperature and with CO-rich compositions. theta(Osub) was measured up to 0.3 monlayer (ML) between 500 and 850 K before the onset of CO adsorption; however, theta(Osub) increases from an insignificant value at <500 K to 0.4 ML at 900 K with a pure O(2) beam. Onset of CO adsorption with a significant sticking coefficient on the Pd surfaces, that is, covered with significant subsurface oxygen, underscores a change in the electronic state of Pd surfaces toward mildly oxidized (or Pd(delta+)), and an electronic decoupling occurs between the bulk and the surface. The jellium model is invoked to demonstrate the changes observed. A similar observation with polycrystalline Pd surfaces suggests the defect sites is one of the channels for oxygen diffusion into subsurfaces. Initial sticking coefficient (s(0)) measurements demonstrate that there is no significant competition between CO and O(2) adsorption from the CO + O(2) mixture between 400 and 600 K, and indeed they are largely independent of each other. The maximum steady-state CO(2) formation rate was observed for a 1:1 CO/O(2) beam composition between 500 and 550 K. However, with a significant theta(Osub) the rate of CO(2) Production in the steady state is considerable even at high temperatures (700-850 K), and a broadening of the active CO oxidation regime to high temperature is observed with O(2)-rich compositions.